Indoor radon, geogenic radon surrogates and geology – Investigations on their correlation. (January 2017) - Friedmann, H.; Baumgartner, A.; Bernreiter, M.; Gräser, J.; Gruber, V.; Kabrt, F.; Kaineder, H.; Maringer, F.J.; Ringer, W.; Seidel, C.; Wurm, G.
Abstract: The indoor radon concentration was measured in most houses in a couple of municipalities in Austria. At the same time the activity concentration of radium in soil, the soil gas radon concentration, the permeability of the ground and the ambient dose equivalent rate were also measured and the geological situations (geological units) were recorded too. From the indoor radon concentration and different house and living parameters a radon potential (Austrian radon potential) was derived which should represent the radon concentration in a standard room. Another radon potential (Neznal radon potential) was calculated from the soil gas radon concentration and the permeability. The aim of the investigation was to correlate all the different variables and to test if the use of surrogate data (e.g. geological information, ambient dose equivalent rate, etc.) can be used to judge the radon risk for an area without performing numerous indoor measurements. Highlights: Radon potential estimation from surrogate data. Different types of geological units often show similar influence on the indoor radon concentration. Correlations between indoor radon concentrations and geological parameters are investigated. Single correlations are often weak but a combination of more parameters show promising results.